KEPENTINGAN BERSAMA PERAWAT-DOKTER DENGAN KUALITAS PELAYANAN KEPERAWATAN - Anggarawati, Tuti; Wulan Sari, Novita (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Nurse is as front line of component health care provider, so it determine the image of hospital. So the quality of nursing care is ahigh impactin the quality of health services. Nurse-physician relationship is a significant role in providing health services to patients. Collaboration between nurse-physician relationships are the foundation of a broader, not only serves to protect the rights, powers and responsibilities of nurses and doctors, but also serves to improve nursing care. This study aimed to know relationship quality nurse-physician collaboration: relationship of common interest with the quality nursing services. The methods used in this study was descriptive analytic cross sectional design of the study on nurses and doctors in general hospitals Tugurejo Semarangin accordance with the inclusion and exclusion criteria of the sample at 186 with a sampling technique in probability sampling with stratified random sampling. Bivariate data analysis using Chi Square.The result show that there are a relationshipof common interest with nursing services (p= 0,000). Â  Keywords : Nursing services, collaboration, common interest